Functional Groups and Individual Phenolic Compounds in Different Fractional Polarities Extracts of Rhizophora apiculata - Othman, Rashidi; Ramya, Razanah; Mohd Hassan, Norazian; Kammona, Suhair (SET PUBLISHER, 2020)
The mangrove forest is often regarded as an unpleasant environment with less intrinsic values. Rhizophora apiculata has an important value as it provides several benefits to people, for example, it is a traditional medicinal plant that is also used in construction, as a source of food, dye and so forth. This study aims to identify types of functional groups and individual phenolic compounds from R. apiculata. An analytical method for R. apiculata was developed with different fractional extracts from water extraction. The result from the FT-IR analysis presented all fractional extract detected with different types of functional groups. The results revealed that four types of individual phenolic acids, which are Caffeic acid, Vanillic acid, trans-p-Coumaric acid and Ferulic acid, were detected in ethyl acetate and butanol extracts. However, none of the phenolic acids was detected in petroleum ether extract. All the phenolic acids detected in the study have not been exploited to their full potential. More research on optimizing the isolation and purification of these pigments as well as their usage in food systems is needed to enable their use in food applications or textile industries.